Mining of potential drug targets through the identification of essential and analogous enzymes in the genomes of pathogens of Glycine max, Zea mays and Solanum lycopersicum. - Rangeline Azevedo da Silva; Leandro de Mattos Pereira; Melise Chaves Silveira; Rodrigo Jardim; Antonio Basilio de Miranda (PLoS ONE, 2018)
Pesticides are one of the most widely used pest and disease control measures in plant crops and their indiscriminate use poses a direct risk to the health of populations and environment around the world. As a result, there is a great need for the development of new, less toxic molecules to be employed against plant pathogens. In this work, we employed an in silico approach to study the genes coding for enzymes of the genomes of three commercially important plants, soybean (Glycine max), tomato (Solanum lycopersicum) and corn (Zea mays), as well as 15 plant pathogens (4 bacteria and 11 fungi), focusing on revealing a set of essential and non-homologous isofunctional enzymes (NISEs) that could be prioritized as drug targets. By combining sequence and structural data, we obtained an initial set of 568 cases of analogy, of which 97 were validated and further refined, revealing a subset of 29 essential enzymatic activities with a total of 119 different structural forms, most belonging to central metabolic routes, including the carbohydrate metabolism, the metabolism of amino acids, among others. Further, another subset of 26 enzymatic activities possess a tertiary structure specific for the pathogen, not present in plants, men and Apis mellifera, which may be of importance for the development of specific enzymatic inhibitors against plant diseases that are less harmful to humans and the environment.